Age‐specific associations of glycated haemoglobin variability with cardiovascular disease and mortality in patients with type 2 diabetes mellitus: A 10‐ year cohort study. Issue 8 (15th April 2020) - Wan, Eric Yuk Fai; Yu, Esther Yee Tak; Chin, Weng Yee; Ng, Florence Ting Yan; Chia, Shu Ming Cheryl; Wong, Ian Chi Kei; Chan, Esther Wai Yin; Lam, Cindy Lo Kuen
Abstract: Aims: To investigate the associations of increased variability in glycated haemoglobin (HbA1c) with cardiovascular disease (CVD) and mortality risk in patients with diabetes. Materials and Methods: This prospective cohort study included 147 811 patients aged 45 to 84 years with type 2 diabetes mellitus, without CVD and with at least three HbA1c values recorded before baseline in the period 2008 to 2010. HbA1c variability was evaluated using a mixed effects model to reduce regression dilution bias. Age‐specific associations (45– 54, 55– 64, 65– 74 and 75– 84 years) between HbA1c variability and risk of CVD and mortality were assessed by Cox regression, adjusted for patient characteristics and usual HbA1c. Results: After a median follow‐up of 7.4 years(1.02 million person‐years), an overall incidence of 40 785 events including CVD (incidence 27  793) and all‐cause mortalities (incidence 23 175) were identified. Positive log‐linear associations between HbA1c variability and CVD and mortality were identified in all age groups. The hazard ratios (HRs) for the composite of CVD and all‐cause mortality showed that age was inversely associated with HbA1c variability, with a 28% higher risk per 1% increase in HbA1c variability in the age group 45 to 54 years (all composite outcomes: HR 1.28, 95% confidence interval [CI] 1.21, 1.35), whereas only a 14% higher risk in the 75– 84 age group (all composite outcomes: HR 1.14, 95% CI 1.11, 1.17). Subgroup analysis showed the risk in patients with usual HbA1c <53mmol/mol was about eight times higher than in those with usual HbA1c ≥64mmol/mol. Conclusions: HbA1c variability was strongly related to CVD and mortality in patients with diabetes across all age groups. Whilst pursuing optimal HbA1c targets, attention should be given to patients with high HbA1c variability, especially younger patients with good HbA1c control.